TIM-3 expression on monocyte-derived dendritic cells - T. V. Tyrinova; O. Yu. Leplina; E. R. Chernykh (Медицинская иммунология, 2024)
The T cell immunoglobulin domain and mucin domain-containing molecule-3 (TIM-3), an inhibitory checkpoint receptor, has been identified as a crucial regulator of cellular immune responses. TIM-3 has been discovered as a receptor involved in the negative regulation of T cells. Recent studies have demonstrated that TIM-3 is expressed on innate immune cells, including dendritic cells (DCs), even at a higher level than T cells. In the tumor microenvironment, the majority of DCs have a monocytic origin. Models for studying such DCs in vitro are DC cultures generated from monocytes in the presence of growth factors. The present study aimed to investigate the expression of TIM-3 in IFNα-induced monocyte-derived DCs (IFN-DCs) and the impact of DC activation on TIM-3 expression. DCs were obtained by culturing the adherent fraction of mononuclear cells from healthy donors for 4 days in the presence of GM-CSF and IFNα, followed by LPS addition for 24 hours. Human double-stranded DNA (dsDNA, 5 μg/mL) was added as an activation stimulus to intact IFN-DCs at the stage of maturation, along with LPS. Expression of the membrane TIM-3 molecule was determined by flow cytometry, and the level of expression of TIM-3 mRNA – by real-time RT-PCR with reverse transcription. Intact donor IFN-DCs expressed the membrane TIM-3 molecule at a high level (more than 70% of cells). The addition of LPS as a maturation stimulus almost halved the expression of TIM-3 (pW < 0.05) without affecting the expression of HAVCR2/TIM-3 mRNA. Exogenous dsDNA (along with LPS) increased the expression of HAVCR2/TIM-3 mRNA by more than three times (pW = 0.05) with a decrease in the number of TIM-3+DCs (pW = 0.003). Our findings indicate the presence of mechanisms that support expression of this inhibitory checkpoint receptor under conditions of DC activation. Further studies of the regulation of TIM-3 expression by monocyte-derived dendritic cells will expand the understanding of the biological significance of inhibitory receptors on DCs from the point of view of the immune response, as well as, in the future, increase the effectiveness of current approaches in cancer immunotherapy using IFN-DCs and inhibitors of checkpoint molecules.